UTILIZATION OF HERBAL PADS TO PREVENT URINARY TRACT INFECTIONS IN WOMEN OF REPRODUCTIVE AGE IN BEJI VILLAGE JUNREJO DISTRICT BATU CITY - Fitria Aisyah; Mufida Annisa R; Woro Tri Utami; Susana Setyowati (CV. Fahr Publishing, 2026)
Urinary Tract Infection (UTI) is a general term used to indicate the presence of microorganisms in urine. Women at high risk for UTIs are menstruating women. In Indonesia, only a small percentage of women use herbal sanitary napkins during menstruation. Therefore, researchers wanted to explore the effect of herbal sanitary napkin use on UTI incidence by assessing urine profiles as an indicator for UTI diagnosis. The research method used in this study was an intervention study with a crossover design. A formula could not be used to determine the sample size because there had been no previous research. Therefore, a sample size of 30 individuals was selected as a preliminary study. The results of the study showed that 1 research subject had leukocytes >15 after using non-herbal sanitary napkins and negative nitrite based on the results of urinalysis using a urine dipstick test. Conclusion: 1. 1 research subject experienced an increase in the number of leukocytes after using non-herbal sanitary napkins. 2. There was no difference in urinary nitrite after using herbal sanitary napkins compared to non-herbal sanitary napkins.